Using Remote Sensing Technology to Detect Changes in the Vegetation Coverage of the Brak-Ashkada Project based on the Normalized Difference Vegetation Index (NDVI) - Ben Youssef خالد علي أحمد; Alshareef إبراهيم (Journal of Pure & Applied Sciences, 2024)
The aims of this study to monitor and evaluate the change in vegetation cover for the agricultural settlement project in Barak Ashkada. The study relied on calculating the Normalized Difference Vegetation Index (NDVI) on the Landsat satellite data for April for the years 1988, 2014, and 2022. The density of vegetation cover in the study area is classified into two classes according to NDVI: an area with no vegetation cover (less than 0.11) and an area with a limited too abundant vegetation cover (greater than 0.11). The results showed that there was a difference in the area and density of vegetation cover during the time of interpretation of satellite images, the year 2014 was more dense, and the percentage of vegetation cover was 55.51%, Then came the year 2022 with a vegetation cover rate of 40.41%, and less in the year 1988 with a vegetation cover area rate of 20.99%. This study demonstrates the potential of remote sensing technologies to provide valuable.